STRATEGI PENINGKATAN EFISIENSI BIAYA BANK UMUM SYARIAH BERBASIS PARAMETIC - Rahmawati, Rafika (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
In the midst of tight competition, Islamic banking is expected to have a good performance in order to compete with conventional banks both local and foreign. The purposes of this study were to analysis the bank cost efficiency level and analysis the effect of input (cost of fund and cost of labor) and output variables (total financing and owned securities). The object of this study is Islamic Banks (BUS) which operates during the period of January 2010 to December 2013. Methods of Stochastic Frontier Approach (SFA) was used to analyze the level of cost efficiency and multiple regression analysis to see the influence of the factors of input and output to the level of cost efficiency. The results showed that the level of efficiency of the BUS is not optimal because there are up to 100%. BMS has the highest efficiency levels. The input and output factors that influence the bank (BUS) cost efficiency level are cost of fund, cost of labor, and total financing.